The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1139/e95-096
|View full text |Cite
|
Sign up to set email alerts
|

Improved age estimates for the White River and Bridge River tephras, western Canada

Abstract: New I4C ages date the eruptions that produced the White River and Bridge River tephras, two important Holocene marker beds in western Canada. The 14C ages were obtained on trees in growth position buried in coarse tephra and a pyroclastic flow near the source vents. The mean calendric age of the White River eruption, based on four I4C ages, is 1147 cal years BP (calibrated years, approximately equivalent to calendric years) or AD 803 (the 2a age range, obtained from the two most precise 14C ages, is 1014-1256 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 23 publications
4
129
0
Order By: Relevance
“…Figure 2 shows a comparison between Eclipse and PRCol records. The PRCol record is placed on a time scale using a model, recent accumulation rates and the major ECM (acid) peaks of Katmai, Laki, a large unknown peak at A.D. 1516 and White River (Clausen et al, 1995;Clague et al, 1995;Zheng et al, 1998;Yalcin and Wake, 2003). The unidentified A.D. 1516 event must be "local" because, although it is the largest peak in the last 550 years, it has no prominence in the Eastern Arctic (Clausen et al, 1995;Zheng et al, 1998).…”
Section: Résumé Comportement Des Isotopes Stables Dans Les Carottes Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows a comparison between Eclipse and PRCol records. The PRCol record is placed on a time scale using a model, recent accumulation rates and the major ECM (acid) peaks of Katmai, Laki, a large unknown peak at A.D. 1516 and White River (Clausen et al, 1995;Clague et al, 1995;Zheng et al, 1998;Yalcin and Wake, 2003). The unidentified A.D. 1516 event must be "local" because, although it is the largest peak in the last 550 years, it has no prominence in the Eastern Arctic (Clausen et al, 1995;Zheng et al, 1998).…”
Section: Résumé Comportement Des Isotopes Stables Dans Les Carottes Dmentioning
confidence: 99%
“…The White River candidate ECM peak stands out and is within a metre of where it is expected. Thus, it is assigned the age of the most recent large eruption (A.D. 803) that deposited the white ash layer over most of southern Yukon (Clague, 1995). Using the time scale for PRCol described in the text, the six largest PRCol ECM peaks coincide with six large sulfate peaks of the Eclipse core over the 530 years.…”
Section: Résumé Comportement Des Isotopes Stables Dans Les Carottes Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristic soils are mildly weathered, alkaline, and have dark A horizons and are classified as Melanic Brunisols. A distinctive component of soil parent materials in southern Yukon is the widespread occurrence of a surface veneer of the late Holocene White River tephra (1147 calibrated years BP; Clague et al 1995). In steeply sloping grasslands, much of the tephra veneer has been modified by organic matter accumulation to form Ah horizons that are generally less than 10 cm thick and overlie buried profiles classified as Melanic Brunisols (Strickland et al 2005).…”
mentioning
confidence: 99%
“…), it was concluded that the tephra originated from the Bridge River eruption ca. 2,410 calendar years ago (Clague et al, 1995). See Appendix C for a microscope image of the glass shards found in the Boswell Lake core.…”
Section: Physical Descriptionsmentioning
confidence: 99%